If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8a + 6a + -2 = 5 Reorder the terms: -2 + 8a + 6a = 5 Combine like terms: 8a + 6a = 14a -2 + 14a = 5 Solving -2 + 14a = 5 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 14a = 5 + 2 Combine like terms: -2 + 2 = 0 0 + 14a = 5 + 2 14a = 5 + 2 Combine like terms: 5 + 2 = 7 14a = 7 Divide each side by '14'. a = 0.5 Simplifying a = 0.5
| (7)(-2)= | | 6x-1+9x+8= | | (3x)(49)=(14x) | | -3(2t+3)=-33 | | 85f=685 | | 5v+x=w^2 | | 15p-5p+4=9 | | -10(s+1)=51 | | 0.72*c=7.5 | | 5x-3+2x=7x+7 | | 48/-16= | | 5x-1=231 | | 3+2(5x+6)=5 | | 5(4s+6)=130 | | h-10=27 | | 8x-19=4-7x | | -1470=-5x-210 | | 8(2l+7)=72 | | -(3+6)+2x=-(6+2)-3.3 | | 14z=18+12z | | -30-29= | | 5x+7=6z | | 12[x]1/3 | | 2y-3=5-s | | 14z=18+12m | | x^2+ab-ax-bx=0 | | 0=-5x-210 | | 2x+1=52 | | (u-8)*10=20 | | 2(-13)=4(16-u) | | 7+h=23 | | 8-c=(-12)-3c |